Cirque du Freak. Volume 9, Killers of the dawn - Shan, Darren (Yen Press, 2011)
Darren, Mr. Crepsley, and Vancha, on the run from the townspeople and the vampaneze, prepare to take a stand when they realize they cannot evade their pursuers, haunted by Lady Evanna's prediction that only one of them would live if they failed to kill the Vampaneze Lord.